2013
DOI: 10.1371/journal.pone.0057753
|View full text |Cite
|
Sign up to set email alerts
|

Born at the Wrong Time: Selection Bias in the NHL Draft

Abstract: Relative age effects (RAEs) occur when those who are relatively older for their age group are more likely to succeed. RAEs occur reliably in some educational and athletic contexts, yet the causal mechanisms remain unclear. Here we provide the first direct test of one mechanism, selection bias, which can be defined as evaluators granting fewer opportunities to relatively younger individuals than is warranted by their latent ability. Because RAEs are well-established in hockey, we analyzed National Hockey League… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 33 publications
(63 reference statements)
7
68
0
Order By: Relevance
“…This is consistent with recent findings in ice-hockey (Deaner, Lowen & Cobley, 2013) and rugby union (McCarthy & Collins, 2014) and supports reductions in relative age biases into adult professional rugby league 12 (Till et al, 2010b). This suggests that relative age advantages, common in youth sport (Cobley et al, 2009), may not be advantageous for long-term performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with recent findings in ice-hockey (Deaner, Lowen & Cobley, 2013) and rugby union (McCarthy & Collins, 2014) and supports reductions in relative age biases into adult professional rugby league 12 (Till et al, 2010b). This suggests that relative age advantages, common in youth sport (Cobley et al, 2009), may not be advantageous for long-term performance.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that relative age advantages, common in youth sport (Cobley et al, 2009), may not be advantageous for long-term performance. A possible explanation for this finding is that the relatively younger individual, selected to a TID programme, may overcome maturational and physical fitness disadvantages and develop heightened technical, tactical and psychological skills to progress in the longer-term if they can persist within developmental programmes (Cobley et al, 2009;Deaner et al, 2013;McCarthy & Collins, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have found relative age effects especially in the educational and athletic context (e.g. (Deaner et al 2013), for a review see (Doblhammer 2004)). In Austria at the beginning of the twentieth century school started on October 1, and children who had not turned six before this date had to wait another year.…”
mentioning
confidence: 99%
“…Relative age effects have been studied extensively in many team sports, including hockey (8,9,33), soccer (15)(16)(17)22,24,31,34), baseball (8,14,35,37), and basketball (7,8,11). In most team sports, RAEs are predominantly seen in youth levels of play and disappear as athletes' progress to the professional ranks (6,15,22).…”
Section: Introductionmentioning
confidence: 99%
“…The NFL draft is similar to the promotion from U-21 to the professional ranks in European soccer clubs as they both represent a player advancing to the highest level of competition. As RAEs have been associated to biased talent selection (9,12,16,25,40), the prospects selected to NFL teams represent an ideal sample in which to examine this phenomenon. Therefore, the purpose of this study is to evaluate the existence of RAEs amongst prospective NFL athletes selected during the NFL draft.…”
Section: Introductionmentioning
confidence: 99%